Physiological characterization of formyl peptide receptor expressing cells in the mouse vomeronasal organ - Ackels, Tobias; von der Weid, Benoît; Rodriguez, Ivan; Spehr, Marc (Frontiers in Neuroanatomy, 2014)
The mouse vomeronasal organ (VNO) is a chemosensory structure that detects both hetero- and conspecific social cues. Based on largely monogenic expression of either type 1 or 2 vomeronasal receptors (V1Rs / V2Rs) or members of the formyl peptide receptor (FPR) family, the vomeronasal sensory epithelium harbors at least three neuronal subpopulations. While various neurophysiological properties of both V1R- and V2R-expressing neurons have been described using genetically engineered mouse models, the basic biophysical characteristics of the more recently identified FPR-expressing vomeronasal neurons have not been studied. Here, we employ a transgenic mouse strain that coexpresses an enhanced variant of yellow fluorescent protein together with FPR-rs3 allowing to identify and analyze FPR-rs3-expressing neurons in acute VNO tissue slices. Single neuron electrophysiological recordings allow comparative characterization of the biophysical properties inherent to a prototypical member of the FPR-expressing subpopulation of VNO neurons. In this study, we provide an in-depth analysis of both passive and active membrane properties, including detailed characterization of several types of voltage-activated conductances and action potential discharge patterns, in fluorescently labeled versus unmarked vomeronasal neurons. Our results reveal striking similarities in the basic (electro)physiological architecture of both transgene-expressing and non-expressing neurons, confirming the suitability of this genetically engineered mouse model for future studies addressing more specialized issues in vomeronasal FPR neurobiology.